2019
DOI: 10.1161/jaha.118.011220
|View full text |Cite
|
Sign up to set email alerts
|

Native Coronary Collateral Microcirculation Reserve in Rat Hearts

Abstract: Background We occasionally noticed that native collateral blood flow showed a recessive trend in the early stages of acute myocardial infarction in rats, which greatly interferes with the accurate assessment of native collateral circulation levels. Here, we sought to recognize the coronary collateral circulation system in depth, especially the microcirculation part, on this basis. Methods and Results In this study, we detected native collateral flow with positron emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In the early stage of AMI, the change in the number of open CCMR vessels showed a parabolic trend, resulting in instability of perfusion blood flow in the ischemic area. When the LAD was ligated for 5 min, the CCMR vessels were almost completely open [1]. The lectin-labeled vessels (green) of the same month-old rats in the 4-h group were reduced by approximately 60% compared with the 5-min group (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the early stage of AMI, the change in the number of open CCMR vessels showed a parabolic trend, resulting in instability of perfusion blood flow in the ischemic area. When the LAD was ligated for 5 min, the CCMR vessels were almost completely open [1]. The lectin-labeled vessels (green) of the same month-old rats in the 4-h group were reduced by approximately 60% compared with the 5-min group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Coronary collateral microcirculation reserve (CCMR), which is a native and potential vessel in the adult healthy rat heart, is recruited immediately after acute myocardial infarction (AMI). CCMR can provide transient blood flow for the ischemic myocardium to prevent or reduce ischemic myocardium injury [1-4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During AMI, a large number of CCMR vessels were recruited to regulate coronary blood flow and myocardium perfusion. However, our further research showed that CCMR vessels of normal adult rats have natural defects in structure, as indicated by discontinuous basement membranes, less vascular endothelial cadherin (VE-cadherin) assembly and greater permeability [6]. VE-cadherin, one of the proteins forming the adherens junctions, plays an important role in maintaining vascular integrity and stability [7][8][9].…”
Section: Introductionmentioning
confidence: 91%
“…In order to explore the relationship between PEDF induced vascular remodeling and the Notch1 signaling pathway in vitro, we established the cardiac explant angiogenesis model as previously described [6,28]. Put simply, we cut and rinsed the cardiac explants (1-2mm 3 ) from neonatal Sprague-Dawley rats (1-3 days old, weighing 6.00.5 g).…”
Section: Cardiac Explant Angiogenesis Modelmentioning
confidence: 99%